Antecedents of Customer Loyalty to Increase Banking Market Share in the Marketing 5.0 Era - sihombing, Margaret; Zulfitri, Zulfitri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2024)
The application of marketing 5.0 in banking industry supports the concept digital banking involving an approach that is more humanity and personality. The concept digital services banking expected to improve customer loyalty and customer re-intention of services banks. This research aims to determine the influence of digital banking services, marketing 5.0 and customer knowledge toward customer re-intention mediated by customer loyalty in customer Bank Indonesia Tangerang branch. The sampling method used non-probability sampling technique, involving 200 respondents. Data analysis used SmartPLS version 3.0. The research results show that: Digital banking services don’t have significant effect on customer loyalty but have positive and significant effect on customer re-intention; Marketing 5.0 and customer knowledge have significant positive effect on customer loyalty but do not have a significant positive effect on customer re-intention; Customer loyalty has a significant positive effect on customer re-intention. And then, customer loyalty only can be mediating effect of customer knowledge on customer re-intention of banking services. Keywords: Customer knowledge, Customer Re-intention, Loyalty, Digital banking services, and Marketing 5.0